Analysis of Junior High School Students' Mathematical Problem Solving Ability on SPLDV Material - Haryanto Pamungkas; Gunawan Gunawan (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to analyze the problem-solving ability of junior high school students in solving the Two-Variable Linear Equation System (SLSE) based on Polya's problem-solving stages. The subjects of this study were grade VIII students at SMP Negeri 2 Cilongok. The research method used was descriptive qualitative with instruments in the form of problem-solving tests and interviews. The results showed that students' problem-solving abilities varied, with most students having difficulty at the stage of understanding the problem and re-checking the solutions obtained. Factors that influence students' difficulties include low understanding of the basic concepts of SLSE and inadequate arithmetic operations. The recommendation in this study is the importance of implementing problem-solving-based learning methods to improve students' abilities.